El proceso de sinecismo del Ática: cultos, mitos y rituales en la «primera polis» de Atenas - Valdés Guía, Miriam (Gerión. Revista de Historia Antigua, 2001)
The synoykismos of Attica, which has been submitted to a long discussion in the past years, may be better understood if it is considered as a long process, situated at the end of the dark ages and the beginning of the archaic period, in the moment of the emergence of the polis. In this perspective, archaic myths, legends and festivals, always constrasted with the archaeological sources, can help to illuminate this process in which we have delineated two significant moments associated to two festivals of the city, the Panathenaia and the Synoikia.